Interrelations of vitamin D status with adiposity and muscle mass in adult women - Rula Amr (BMJ Nutrition, Prevention & Health)
Background Vitamin D deficiency (VDD) is common among women, particularly those with central adiposity. This study examines the predictors of vitamin D levels, focusing on age, adiposity and muscle composition.Methods A cross-sectional study was conducted with 397 women aged 18–59 years in Jordan. Vitamin D levels were measured using high-performance liquid chromatography. Anthropometric and body composition metrics, including fat-free mass index, conicity index, body mass index (BMI) adjusted skeletal muscle mass index (SMI BMI) and central adiposity measures (waist circumference (WC) and waist-to-hip ratio (WHR)), were analysed. Statistical analyses included χ2 tests, t-tests and multivariable Lasso regression.Results Age was the strongest predictor of vitamin D levels, with older women exhibiting higher mean concentrations (42.80±11.01 years in the adequate group vs 36.45±11.22 years in the inadequate group; p<0.001). Central adiposity measures were significantly associated with vitamin D adequacy: WC<88 cm (73.8% vs 5.0%, p<0.001) and WHR<0.85 (20.3% vs 9.1%, p=0.001). Generalised adiposity measures, including BMI, were not significant in univariate analysis (p=0.668), but BMI was a negative predictor in Lasso regression (β=−1.078, 95% CI −1.400 to −0.756). SMI BMI showed a borderline negative association (p=0.054).Conclusions Age and central adiposity are the key predictors of vitamin D levels, emphasising the importance of fat distribution over generalised measures. Public health strategies should target central adiposity and muscle health, especially in younger women at risk of VDD.